2005
DOI: 10.1080/15732480500125593
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stresses in steel girder bridges with integral abutments

Abstract: This paper demonstrates the use of field measurements to evaluate the performance of integral abutment bridges and to check the validity of the design assumptions. A newly constructed integral abutment bridge was heavily instrumented to monitor its long-term performance under the effects of environmental conditions and traffic loading. The collected data indicate that integral abutments resist the expansion of the bridge superstructure during summer time, leading to excessive axial compressive forces in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…A laboratory study to develop a comprehensive small scale instrumentation system for bridge monitoring demonstrated that reliable and feasible bridge monitoring systems was achievable [5]. Implementations of sensor-based health monitoring systems on existing bridges demonstrated the ability of such systems to render valuable data [6][7][8][9][10][11][12][13]. The use of dynamic techniques to evaluate bridge damage in the field proved to be useful tools.…”
Section: Introductionmentioning
confidence: 99%
“…A laboratory study to develop a comprehensive small scale instrumentation system for bridge monitoring demonstrated that reliable and feasible bridge monitoring systems was achievable [5]. Implementations of sensor-based health monitoring systems on existing bridges demonstrated the ability of such systems to render valuable data [6][7][8][9][10][11][12][13]. The use of dynamic techniques to evaluate bridge damage in the field proved to be useful tools.…”
Section: Introductionmentioning
confidence: 99%
“…Many field studies were conducted during the last 30 years to better understand the temperature distributions and their structural effects on concrete, steel, and composite bridge structures. Generally, field studies are sponsored by the transportation agencies as parts of complete long‐term structural health monitoring (SHM) projects.…”
Section: Introductionmentioning
confidence: 99%
“…support piers, abutments, bents). Additionally, restrained thermal deformation has been found to negatively affect the structural capacity of the steel girders themselves in studies by William et al (2005) and McBride (2013). Preventing, or at the least minimizing, the development of thermal stresses in a steel girder bridge system is generally accomplished through the strategic employment of bridge expansion bearings.…”
Section: Response Of Steel Girder Bridges To Temperature Variationsmentioning
confidence: 99%
“…If thermal deformation of a bridge's steel superstructure is not freely allowed, or if thermal movements become restrained during the life of the structure, thermal force effects will develop throughout a continuous bridge, negatively influencing its structural integrity. William et al (2005) and McBride (2013) showed that when restrained, thermal expansion of a steel girder superstructure can lead to relatively large thermal stresses that reduce the expected structural capacity of the steel I-girders.…”
mentioning
confidence: 99%
See 1 more Smart Citation